Three Monthly Intravenous Injections of Ibandronate in the Treatment of Postmenopausal Osteoporosis (Medical Forum Monthly, 2024)
Background: Osteoporosis is a chronic condition that generally requires long-term therapy for fracture risk reduction to become apparent. Bisphosphonates are important therapeutics in postmenopausal osteoporosis. However, they are currently associated with stringent dosing instructions that may impair patient compliance and hence therapeutic efficacy. Intravenous (IV) treatment with an aminobisphosphonate, pamidronate was effective, but required infusions. Ibandronate, a new very potent aminobisphosphonate, can be administered safely as an IV bolus injection, and therefore offers an interesting alternative suitable for outpatient treatment.Objective: To determine the effectiveness of three monthly IV bolusIbandronate injections in terms of increase in bone mineral density at hip and spine in postmenopausal women.Study Design: Randomized Placebo controlled study.Place and Duration of Study: This study was conducted in Gynae “B” Unit of Khyber Teaching Hospital, Peshawar from Feb 2012 to Jan 2013Materials and Methods: 150ambulatory Postmenopausal women 55-75 years old, and atleast 5years since menopause with osteoporosis ((bone mineral density [BMD] < −2.5 SD T score) received a placebo or IbandronateIV bolus injection(3 mg) every 3 months. All patients received 1 g calcium/day. BMD, expressed in T score, was measured by dual-energy x-ray absorptiometry (DEXA) at lumbar spine and hip. Exclusion criteria were a disease, disorder, or therapy (within the last 6 months) known to influence bone metabolism; prior treatment with oral or intravenous bisphosphonates; Baseline radiographic assessment for prevalent vertebral fractures was not performed in this study. All participants provided written informed consent.Results: There were 150 Postmenopausal women with mean age of 62 years.Lumbar spine BMD (L2 to L4) decreased by 2.9% and hip by 3.2% in the placebo group, but increased by 5.2% at 12 months for Ibandronategroup. The increase was statistically significantly different from placebo (P < 0.001) group. After 1 year total hip BMD increased significantly by 4.5%.Conclusion: Treatment of postmenopausal osteoporosis by interval IV bolus injections of the bisphosphonate Ibandronateis an effective and convenient way of increasing BMD at hip and spine. The high potency of Ibandronate allows 3-month interval bolus IV injections as a new therapeutic approach with optimal compliance.